Chemical analysis and bioactive compounds from agrifood by-products of peruvian crops - Inga, Marianela; Betalleluz-Pallardel, Indira; Puma-Isuiza, Gustavo; Cumpa-Arias, Leslie; Osorio, Coralia; Valdez-Arana, Jenny-Del-Carmen; Vargas-De-La-Cruz, Celia (Frontiers in Sustainable Food Systems, 2024)
Many countries face the problem of agroindustrial waste elimination, which is linked to environmental damage caused by improper waste management. These wastes contain bioactive compounds often discarded due to a lack of knowledge. The objective of this study was to analyze five types of agroindustrial waste from Peru, including avocado (Persea americana) seeds, lucuma (Pouteria lucuma) seeds, grape (Vitis vinifera) pomace, mango (Mangifera indica) peel, and cocoa (Theobroma cacao) pods. This study includes proximal analysis, determination of total phenolic compound content, analysis of phenolic compounds by UHPLC– Q/Orbitrap/ESIMS/MS (Ultrahigh-performance liquid chromatography-electrospray ionization Q-Orbitrap mass spectrometry), and the evaluation of antioxidant, antimicrobial, and antifungal activities of different samples. The results showed that lucuma seeds had the highest protein content of 6.59 g/100 g DW. Mango peels showed the highest fat content of 4.89 g/100 g DW, cocoa pods had the highest crude fiber content of 26.91 g/100 g DW, and cocoa pods exhibited the highest ash content of 7.14 g/100 g DW. The highest carbohydrate content was found in avocado seeds at 85.85 g/100 g DW. Mango peels (56.66 mg GAE/g DW), avocado seeds (56.35 mg GAE/g DW), and cocoa pods (51.52 mg GAE/g DW) extracts showed the highest phenolic compound contents. Mango peel extract exhibited the highest antioxidant activities evaluated by the ABTS (995.01 μmol TEAC/g DW), DPPH (953.54 μmol TEAC/g DW), and FRAP (1661.13 μmol TEAC/g DW) assays. Extracts from cocoa pods, grape pomace, and lucuma seeds showed inhibitory activity on the growth of Staphylococcus aureus and Escherichia coli. In contrast, the extract of lucuma seeds was the only one that showed antifungal activity over Penicillium digitatum. As a result, several phenolic compounds were detected in each, indicating their potential use in developing functional foods and food preservation, among other applications.